1990
DOI: 10.1149/1.2086651
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Ta2 O 5 Films by LPCVD for ULSI Application

Abstract: Preparation and electrical properties of tantalum pentoxide (Ta20~) films have been studied for the application to ultra large scale integrated circuits (ULSIs). Ta205 films were deposited by a cold wall-type low-pressure chemical vapor deposition (LPCVD) at temperatures of 340~176 and then annealed at temperatures ranging from 600 ~ to 900~ in 02. It can be found that for the films grown by the present method, a high-temperature annealing is exceedingly effective for an increase in dielectric constant and a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…While the similar experimental observations have been made by a few research groups, 5,7 other groups observed opposite results. 4,8 The cause of different observations seems to originate from the O 2 annealing conditions. Oehrlein et al 9 reported that the higher temperature annealing could lead to the higher leakage current.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the similar experimental observations have been made by a few research groups, 5,7 other groups observed opposite results. 4,8 The cause of different observations seems to originate from the O 2 annealing conditions. Oehrlein et al 9 reported that the higher temperature annealing could lead to the higher leakage current.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 Zaima et al 4 showed that the leakage current density decreased continuously as the annealing temperature increased up to 900°C Aoyama et al, 5 however, reported that the leakage current started to increase after the Ta 2 O 5 was crystallized at a temperature of 700°C. Kim et al 3 also found that the leakage current of the film abruptly increased after annealing at 856°C.…”
Section: Introductionmentioning
confidence: 99%
“…As in complex 1, the dbm b-diketonate ring is planar and symmetrical, with entirely typical C±C and C±O bond lengths. [25] The major distortion from ideal octahedral geometry occurs along the O(4)±Nb(1)±O(1) axis (163.86(12)), and the cis O±Nb±O bond angles also show a significant deviation from the ideal 90, varying in the range 80.08(10)± 100.38 (12). The bite angle of the dbm ligand in 2 is 80.08(10), very close to the dbm bite angles of 80.5 (2) and 79.9(3) in 1, and the b-diketonate bite angles in Ta-(OMe) 4 (acac) [22] and Ta(OMe) 4 (thd) [22] of 78.9(5) and 79.3(2), respectively.…”
Section: Crystal Structures Of 1 Andmentioning
confidence: 99%
“…[7] Niobium oxide has applications in SrBi 2 Nb 2 O 9 non-volatile ferroelectric memory layers, [8] and in the Pb(Mg 0.33 Nb 0.66 )O 3 films used in transducers and electroceramic capacitors. [9] A variety of techniques, including reactive sputtering, [10] sol±gel deposition, [11] and MOCVD, [1,2,12,13] have been used for the deposition of Ta 2 O 5 and Nb 2 O 5 thin films. Of these techniques, MOCVD offers the most flexible approach, having the advantages of large area deposition capability, good composition and thickness control, and excellent conformal step coverage on complex structures.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical vapour deposition using Ta(OC2Hs)5 can lead to Ta205 films [1,2] which are relevant to storage capacitors in memory cells and gate insulators in ultrahigh-density integrated circuits, because of their high-dielectric constant (i.e., up to 35 for crystallized/%Ta205 [3]) and because of their high index of refraction (2.03-2.8 [4,5]) for highly reflective (HR) mirrors [6][7][8]. The latter application depends on a refractive index for Ta205 which is higher than ZrO2 (1.72), but lower than that for TiO2 (2.3) [4].…”
Section: Introduction 2 Experimentalmentioning
confidence: 99%